Social Insurance, Informality and Labor Markets: How to Protect Workers While Creating Good Jobs - Carmen Pagés; Jamele Rigolini; David A. Robalino (Institute for the Study of Labor (IZA), 2013)
This paper provides an overview of the main findings of the book Social Insurance and Labor Markets: How to Protect Workers While Creating New Jobs. The book conceptualizes and reviews the empirical evidence on the potential distortions that the social insurance system of a country can have on the supply and demand side of the labor market, and proposes options to address them. The overall message is that current Bismarckian systems are inadequate to extend coverage to the entire labor force of a country and that, at the same time, can affect the level and structure of employment for instance, by promoting informality and reducing participation rates. These effects can be important enough to deserve consideration in policy discussion. In part, they are explained by a series of explicit and implicit taxes and subsidies that emerge as part of the design of health insurance, pensions, and unemployment benefits programs. Going forward, there a few general principles that countries can follow to expand coverage while reducing potential distortions in labor markets. First, giving more flexibility to individuals in the choice of the bundle of social insurance programs, the level of benefits, and the portfolio of investments (in the case of savings programs), while providing better information and incentives to enroll. Second, relying on explicit, integrated, and in some circumstances means-tested redistributive arrangements in order to better contribute to reduce poverty and inequality. Finally, from the point of view of labor markets, by aiming to reduce perceived tax-wedges. This could be done by better linking contributions to benefits, improving the quality of services, and financing redistributive arrangements through general revenues.
Keywords: J3; J6; H2; H3; I3; D3; 330; social insurance; pensions; informality; pay-roll taxes; redistribution; labor markets